Membangun Lingkungan Kerja Yang Ergonomis Pada PT Dwi Mitra Teknindo - Busyaro Hasab Najmi Hakim; Muhamad Mahmud Yusup (Jurnal Manajemen Bisnis Digital Terkini, 2024)
An ergonomic work environment is designed to enhance the comfort, efficiency, and well-being of employees by optimizing the interactions between individuals and their workspaces. This approach encompasses the arrangement of furniture, the selection of equipment, and the configuration of the physical workspace to prevent musculoskeletal disorders, reduce fatigue, and improve productivity. Key elements include adjustable chairs and desks, proper lighting, adequate ventilation, and the strategic placement of computer monitors and keyboards. By incorporating ergonomic principles, organizations can mitigate the risk of repetitive strain injuries and other work-related ailments, fostering a healthier and more engaged workforce. The implementation of ergonomic solutions not only contributes to physical health but also supports mental well-being by reducing stress and enhancing overall job satisfaction. As a result, businesses benefit from increased employee performance, lower absenteeism, and a more positive organizational culture.